Adaptation processes in skeletic muscles of handball players - Madzharov, A. P.; Bondarenko, K. K. (Національний технічний університет "Харківський політехнічний інститут", 2019)
The aim of this work was to determine qualitative and quantitative parameters of physical loads of female handball players, based on biomechanical parameters of muscular activity. Parameters used technical-tactical training exercises must be based on the nature of their perception by the athlete’s body. Excessive physical activity may lead to overstrain of the functional systems of the body. This can affect not only the effectiveness of conducting training sessions, but also the result of competitive activities.
Keywords: myometrium; functional condition; skeletal muscles; load parameters